Program Development of Small and Medium Enterprises in Stavropol Region of the Russian Federation - Levushkina, Svetlana Vladimirovna; Miroshnichenko, Ruzanna Vijulovna; Kurennaya, Viktoria Vital’evna; Agalarova, Ekaterina Grigorievna (International Journal of Economics and Financial Issues, 2016)
Development of small and medium enterprise system as a cyclic process with basic principle of the continuity between development cycles and their development programs that provides potential stability of development of small and medium enterprise system in a prospective period has been considered in the paper. Research of the target programs implementation providing actions for support and development of small and medium enterprise in the Stavropol Region has been conducted by the authors. The continuity of actions which is a cornerstone of the accepted programs is established. It forms the potential stability of development of small and medium enterprise system (SME). The article proves necessity for modeling of the SME system development taking into account its cyclicality. Keywords: small and medium enterprises, stability of the system, development program indicators, JEL Classifications: D22, D84, L5, P42